2020
DOI: 10.1111/epi.16503
|View full text |Cite
|
Sign up to set email alerts
|

Late drug‐resistance in mild MTLE: Can it be influenced by preexisting white matter alterations?

Abstract: Objective: To identify early structural alterations preceding the development of drug-resistance in mild mesial temporal lobe epilepsy (mMTLE), a drug-responsive syndrome ideal for investigating epilepsy pathophysiology and potential prognostic markers of long-term clinical outcome, using magnetic resonance imaging (MRI) at baseline and after 12-year follow-up. Methods: Since 2002, a total of 55 participants with a baseline diagnosis of mMTLE underwent three-dimensional (3D) T1 1.5T MRI. Based on long-term out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…In fact, temporal lobe FA was able to differentiate between refractory versus benign TLE with an AUC of 0.74. In a follow-up study, patients whose mild mesial TLE eventually evolved into refractory mesial TLE had distinct microstructural alterations in the corticospinal tracts, superior longitudinal fasciculus, left cingulum, and left inferior longitudinal fasciculus prior to the development of drug resistance (Labate and others 2020). These data suggest that greater WM pathology both within and beyond the temporal lobe may predispose patients to develop drug-resistant seizures.…”
Section: Wm Associations With Cognitive and Psychiatric Comorbiditiesmentioning
confidence: 99%
“…In fact, temporal lobe FA was able to differentiate between refractory versus benign TLE with an AUC of 0.74. In a follow-up study, patients whose mild mesial TLE eventually evolved into refractory mesial TLE had distinct microstructural alterations in the corticospinal tracts, superior longitudinal fasciculus, left cingulum, and left inferior longitudinal fasciculus prior to the development of drug resistance (Labate and others 2020). These data suggest that greater WM pathology both within and beyond the temporal lobe may predispose patients to develop drug-resistant seizures.…”
Section: Wm Associations With Cognitive and Psychiatric Comorbiditiesmentioning
confidence: 99%
“…Furthermore, imaging and post-processing imaging helps to identify early structural alterations preceding the development of drug-resistance in mild mesial temporal lobe epilepsy with LOE and to better understand pathophysiology in such syndrome (38)(39)(40)(41). However, it should be considered that the possibility of identifying some lesions (e.g., focal cortical dysplasia) in patients with LOE is lower compared to younger subjects (8,42,43).…”
Section: Neuroradiologymentioning
confidence: 99%
“…At follow-up, these patients showed decreased fractional anisotropy in the corpus callosum, superior longitudinal fasciculi, and major bundles of the right hemisphere, independently of the presence of HS. 177 In addition, a research protocol for a longitudinal study has been published, aiming to evaluate preexisting brain connectivity, molecular information, and the outcome of pharmacologic treatment in patients with newly diagnosed focal epilepsy. 178 Finally, the contribution of integrating multi-omic data in the study of pharmacoresistant MTLE is still unexplored 179 (Table 7).…”
Section: Final Remarksmentioning
confidence: 99%
“…An interesting prospective study aimed to identify early brain abnormalities that could precede pharmacoresistance in patients with MTLE has recently been published by Labate et al 177 The authors reported that before patients became refractory to ASM, they presented abnormalities in the white matter volume of the arcuate fasciculi, corticospinal tracts, left retrosplenial cingulum, and left inferior longitudinal fasciculus reduced. At follow‐up, these patients showed decreased fractional anisotropy in the corpus callosum, superior longitudinal fasciculi, and major bundles of the right hemisphere, independently of the presence of HS 177 . In addition, a research protocol for a longitudinal study has been published, aiming to evaluate preexisting brain connectivity, molecular information, and the outcome of pharmacologic treatment in patients with newly diagnosed focal epilepsy 178 …”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation